2009
DOI: 10.1007/s12034-009-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanocrystalline mixed metal fluorides in nonaqueous medium

Abstract: Synthesis of mixed metal fluorides of the general formula, KMF 3 (M = Mg, Mn, Co, Ni, Cu and Zn), possessing perovskite structure was investigated in non-aqueous medium. The fluorides were characterized by powder X-ray diffraction, FT-IR spectroscopy, thermal analysis, SEM and TEM. Monophasic cubic phases were obtained for the central metal ions such as Mg, Mn, Co, Ni, and Zn and a tetragonally distorted phase was observed for Cu. The usage of non-aqueous medium is advantageous for the bulk synthesis of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…Monoclinic KSnF 3 was synthesized by a simple and green precipitation reaction of SnCl 2 ·2H 2 O and KF in methanol as reported for other KMF 3 fluoride complexes . The powder X-ray diffraction pattern of KSnF 3 is presented in Figure a, which matched well with JCPDS file no.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Monoclinic KSnF 3 was synthesized by a simple and green precipitation reaction of SnCl 2 ·2H 2 O and KF in methanol as reported for other KMF 3 fluoride complexes . The powder X-ray diffraction pattern of KSnF 3 is presented in Figure a, which matched well with JCPDS file no.…”
Section: Resultssupporting
confidence: 64%
“…Our research group has reported green synthetic approaches for various mixed metal fluoride complexes . KSnF 3 was synthesized from SnCl 2 ·2H 2 O (99.9%, Aldrich) and KF (99%, AR grade, CDH) in a 1:3 molar ratio.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The molecular orbital coefficients N x and x are acquired for the anti-bonding and bonding orbitals from Eqs. (5)- (7). Applying Eqs.…”
Section: Theory and Calculationsmentioning
confidence: 99%
“…Fluoroperovskites ABF 3 (A = K, Cs and B = Zn, Mg, Cd, Ca) doped with Mn 2+ show unique photo and thermostimulated luminescence [1], mechanoluminescent [2], dielectric [3], optical [4] and structure properties [5][6][7]. Usually, the doped Mn 2+ impurities may play an important role in the above properties.…”
Section: Introductionmentioning
confidence: 99%